Bank Lending to the Commercial Real Estate Sector - a Source of Systemic Risk? - Marius Hagen; Ida Nervik Hjelseth; Haakon Solheim; Bjørn Helge Vatne (Norges Bank, 2018)
Banks' commercial real estate loans account for almost half of banks' total loans to non-financial enterprises. Losses on these loans are normally low in good times, but they have proved to be one of the largest sources of bank losses in financial crises. As there is often a mismatch between the maturity of a bank's commercial real estate loan and the lifetime of a property, there is a risk that banks do not adequately price in losses on commercial real estate loans incurred during crises. This article further argues that financial risk is particularly high in the office segment. Prices in Oslo are currently elevated, vacancy rates are low and construction in recent years has been limited. Structural factors are restraining speculative construction. A tight market on the supply side may contribute to reducing the risk of a substantial price adjustment even if yields should rise.
hdl:11250/2581808
Keywords: 330